Long-Term Topical Diquafosol Tetrasodium Treatment of Dry Eye Disease Caused by Chronic Graft-Versus-Host Disease: A Retrospective Study. (November 2018) - Yamane, Mio; Ogawa, Yoko; Fukui, Masaki; Kamoi, Mizuka; Uchino, Miki; Saijo-Ban, Yumiko; Kozuki, Naoyuki; Mukai, Shin; Mori, Takehiko; Okamoto, Shinichiro; Tsubota, Kazuo
Abstract : Objectives: The aim of this study was to assess the safety and efficacy of long-term use of 3% diquafosol ophthalmic solution (DQS), an eye drop for mucin production and water secretion, for treating dry eye disease (DED) caused by chronic graft-versus-host disease (cGVHD). Methods: We retrospectively evaluated the safety and efficacy of DQS in 10 patients with mild to moderate cGVHD-induced DED. The efficacy was assessed by (1) degree of symptoms, (2) Schirmer I test value, (3) tear film breakup time (TFBUT), and (4) fluorescein and rose bengal scores. Results: The median duration of DQS treatment was 12.0 months (range 6–17 months). DQS was effective for relieving severe pain caused by cGVHD-related DED. Although the Schirmer I test value was enhanced only marginally, the long-term application of DQS significantly improved the corneal/conjunctival epitheliopathy and tear film stability: the fluorescein score improved from 5.9±0.6 to 1.3±1.1 points ( P =1.771×10 −5 ); rose bengal staining from 4.7±1.6 to 2.0±1.5 points ( P =0.008); and TFBUT from 2.6±0.9 to 4.6±1.6 mm ( P =0.009). Furthermore, the long-term DQS treatment caused no major adverse events. Conclusions: This study suggested that long-term DQS treatment is a safe and robust approach for alleviating cGVHD-related DED.